Nuclear energy an introduction to the concepts, systems, and applications of nuclear processes - Murray, Raymond L., 1920-2011. (Boston : Butterworth-Heinemann, 2001)
Nuclear Energy, Fifth Edition provides nuclear engineers, plant designers and radiation physicists with a comprehensive overview of nuclear energy and its uses, discusses potential problems and provides an outlook for the future New and important trends are discussed including probabilistic safety analysis (PSA), deregulation of the electric power industry to permit competition in the supply of electricity; improvements in performance characteristics of nuclear power plants, such as capacity factor, production costs, and safety factors; storage and disposal of all types of radioactive wastes; advances in decontamination, decommissioning and reutilization; continued progress in evolutionary reactors; increased interest in the role of nuclear power in reducing pollution and global warming. Attention will also be given to the developments in such countries as Russia, Ukraine, France, Sweden, South Korea, China and Third World Countries. The author also looks at the problems of nuclear weapons proliferation and the potential threat from terrorist organizations or reckless countries. In addition, the author has identified Web sites and other electronic information sources to supplement all of the topics covered in this book. * Latest edition with updated content in important subject areas * Free downloadable software accompanies book contents * Revised instructor's manual to accompany book.
Energy -- Atoms and nuclei -- Radioactivity -- Nuclear processes -- Radiation and materials -- Fission -- Fusion -- Particle accelerators -- Isotope separators -- Radiation detectors -- Neutron chain reactions -- Nuclear heat energy -- Breeder reactors -- Fusion reactors -- The history of nuclear energy -- Biological effects of radiation -- Information from isotopes -- Useful radiation effects -- Reactor safety -- Nuclear propulsion -- Radiation protection -- Radioactive waste disposal -- Laws, regulations, and organizations -- Energy economics -- International nuclear power -- Nuclear explosions -- The future.
Includes bibliographical references and index.
Keywords: Nuclear engineering; Nuclear energy; Electronic books